Scalable alcohol interventions - An online "Month off Booze" programme - Jussi Tolvi (Frontiers Media S.A., 2015)
Background Alcohol misuse is one of the biggest public health issues in the UK. Mobile and internet interventions for public health promotion are cost-effective, and have been shown to have some efficacy. However, many do not lead to much (if any) long-term impact. On the other hand, more intensive and longer-term intervention are also more expensive and often difficult to scale. We describe a scalable online intervention supporting people who want to abstain from alcohol for a month. Description Club Soda - To create an approach that combines the best features from both online and face to face interventions, Club Soda works on a blended model combining both types of activities. Our aim is to offer a large number of behaviour change tools and techniques in one place. Online, this includes goal setting and progress tracking, information, email prompts, a mutual aid community, and links to expert support and distractions. We also organise pub socials with volunteer members, as well as expert-led workshops providing more intensive support for those who need it. Online "Month Off Booze" programme - Club Soda's MOB (Month Off Booze) programme is a way of scaling our model to reach a larger audience. The programme was developed to support people who have decided to abstain from alcohol for a month. There are several well-known such campaigns in the UK, encouraging people both to abstain for a month and raise funds for charity (e.g. Dry January and Go Sober for October). The main content of the MOB programme consist of daily email prompts, and a dedicated website with a variety of information from alcohol harms to behavioural techniques and non-alcoholic drink suggestions. This content combines a number of behaviour change techniques, from planning and goal setting to tracking progress and peer support. An online forum provides a place for participants to talk with each other, and for the experts involved in the programme (a psychologist, a nutritionist, and a life coach) to answer any questions. There are also weekly web socials and webinars for further interaction, and optional additional activities such as face to face workshops (e.g. on learning how to control stress), pub socials and other activities during the month. The pilot MOB programme was set up to coincide with the "Sober October" campaign. Using learning from this pilot, we will roll out the next programme in time for "Dry January". We will also create a modified version of the programme that can be completed at any time (the main difference is the absence of live webinars in the "anytime" version). Feedback and evaluation - The initial feedback from participants has been very positive. We are collecting data throughout the month (in fact over 40 days, with a week for pre-planning and three days for reflection afterwards). All participants are asked to complete an AUDIT C questionnaire before the programme begins, weekly progress updates on several aspects of their life (sleep, moods, cravings etc), on how many days during the previous week they've drank alcohol, and their confidence and commitment to staying sober for the month. And we will get qualitative data from the online forum discussions and questions asked at the webinars and so on. Conclusions Club Soda has developed a scalable online intervention, supporting people who want to abstain from alcohol for a month, which will be piloted in October 2015. An evaluation of the programme is not possible at the time of writing this abstract, but will be completed in November 2015. Based on initial feedback and anecdotal evidence, however, the programme is expected to be a powerful tool helping people abstain for a set period of time, and in reducing their alcohol consumption after the programme as well.